Peritoneal dialysis-associated peritonitis caused by Enterococcus avium. Issue 3 (24th March 2021) - Calça, Rita; Gomes da Silva, Francisca; Martins, Ana Rita; Branco, Patrícia Quadros
Abstract : Peritonitis remains a common and serious complication of peritoneal dialysis. Peritonitis caused by gram-positive organisms includes coagulase-negative staphylococci, Streptococcus spp and Enterococcus spp. We present a rare case of peritoneal dialysis-associated peritonitis, where persisting abdominal pain and worsening laboratory findings despite antibiotic therapy led to the identification of Enterococcus avium, requiring Tenckoff catheter removal and temporary transfer to haemodialysis. The available literature reports only few cases where peritonitis is caused by this agent, underlining the need to consider atypical microbial agents when heterogeneous clinical course is presented.